Penyalahgunaan Kewenangan Pejabat Pemerintahan Dan Ruang Lingkupnya Menurut Undang-Undang Administrasi Pemerintahan - Barhamudin, Barhamudin (Solusi, 2019)
The purpose of this research is to find out, study and analyze in determining the element of abusing authority in government administrative laws. In this study using normative research with a statutory approach and a conceptual approach. Legal materials consisting of Primary Legal Materials, Secondary Legal Materials and Tertiary Legal Materials. The results obtained are benchmarks to determine the existence of abuse of authority according to administrative law, in this case UUAP occurs if government officials or officials conduct discretion without going through procedures and the purpose is not carried out within the scope of what has been determined by Law of the Republic of Indonesia Number 30 of 2014 concerning Government Administration in article 17 and article 18 includes: a. The statute goes beyond the authority; b. prohibition of confusing authority; c. prohibition of arbitrary actions. d. beyond the term of office or the validity period of the Authority; e. beyond the territorial validity of the Authority; and / or f. contrary to statutory provisions. g is outside the scope of the field or material given Authority; and / or h. contrary to the stated purpose of the Authority. Abuse of authority either according to administrative law or criminal law has the respective legal domain. Decisions and / or Actions that are determined and / or carried out by exceeding illegitimate Authority if it has been tested and there is a Court Decision that has permanent legal force and Courts that have permanent legal force.